Low CD4 count and educational status predict abnormal cervical smears amongst HIV-positive women initiating antiretroviral therapy in South Africa - Mthembu, N; Dorward, J; Naicker, N; Osman, F; Gumede, S; Sookrajh, Y; Drain, P; Garrett, N (AOSIS, 2020)
Cervical cancer is common amongst human immunodeficiency virus (HIV)-positive women in low- and middle-income countries. In South Africa, more than 7500 cases are diagnosed annually and over 50% result in death, making cervical cancer the leading cause of cancer mortality.1 South Africa’s high HIV prevalence contributes to this high burden, because HIV-positive women are more likely to have persistent human papilloma virus (HPV) infection and precancerous cervical changes.2 Cervical cancer is preventable either through HPV vaccination of girls before sexual debut, which was rolled out in South Africa from 2014, or screening and treatment of precancerous cervical lesions. South African guidelines recommend cervical screening for all HIV-positive women at HIV diagnosis and then every 3 years.1 Antiretroviral therapy (ART) causes immune reconstitution and may reduce the risk of cervical cancer amongst HIV-positive women by lowering HPV acquisition, increasing HPV clearance and slowing the progression to precancerous lesions.2 However, these effects may be diminished for women who initiate ART at low CD4 counts.3 Since 2016, when universal test and treat (UTT) was introduced in South Africa, women began initiating ART at CD4 counts > 500 cells/mm3 (early initiators) and may therefore be protected against precancerous cervical abnormalities and cancer.3 In this study, we aimed to assess whether early initiators of ART had a lower risk of abnormal cervical smears when compared to late initiators (women with a CD4 ≤ 500 cells/mm3 ), after introduction of UTT in South Africa.